PENGEMBANGAN MEDIA ASESMEN PEMBELAJARAN BERBASIS WORDWALL PADA MATERI SIFAT ALLAH SWT TERHADAP MINAT SISWA KELAS VII MTS TERPADU BERKAH PALANGKA RAYA - Anhu Raja; Gunanti Gunanti; Lijar Pastilah (ADIBA : JOURNAL OF EDUCATION, 2024)
This research aims to develop Wordwall-based learning assessment media on the nature of Allah SWT in class VII at MTs Terpadu Berkah Palangka Raya. Using the "Research and Development" (R&D) method, this research involves validation by material and media experts, which shows results that are worthy of being tested. Product trials show that this media can increase students' interest and motivation in the learning process. The research results show that 81% of students feel more enthusiastic when using this media, while 76% of teaching staff support its implementation. Wordwall-based assessment media not only helps understanding the material, but also creates a more interactive and interesting learning atmosphere, so that it can overcome limited infrastructure and policies in schools.